2013
DOI: 10.1161/circgenetics.113.000057
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Novel Mutation in NKX2-5 Associated With Congenital Heart Disease and Adult-Onset Cardiomyopathy

Abstract: Background The transcription factor NKX2-5 is crucial for heart development and mutations in this gene have been implicated in diverse congenital heart diseases (CHD) and conduction defects (CD) in mouse models and humans. Whether NKX2-5 mutations have a role in adult-onset heart disease is unknown. Methods and Results Mutation screening was performed in 220 probands with adult-onset dilated cardiomypathy (DCM). Six NKX2-5 coding sequence variants were identified, including 3 non-synonymous variants. A novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 46 publications
(85 reference statements)
2
74
1
Order By: Relevance
“…dilated cardiomyopathy as already observed in two previous reports. 14,15 Family MC177 is interesting because the maternal grandmother had a D-TGV and carried the heterozygous ZIC3 diseasecausing variant, suggesting that this variant could be dominant or that she had an unbalanced X inactivation as already shown in two other familial cases. 16,17 It is much easier in familial cases to infer the putative causal gene than in sporadic cases, because in familial cases the spectrum of phenotypic anomalies is broader by compiling the various anomalies of affected relatives.…”
Section: Discussionmentioning
confidence: 75%
“…dilated cardiomyopathy as already observed in two previous reports. 14,15 Family MC177 is interesting because the maternal grandmother had a D-TGV and carried the heterozygous ZIC3 diseasecausing variant, suggesting that this variant could be dominant or that she had an unbalanced X inactivation as already shown in two other familial cases. 16,17 It is much easier in familial cases to infer the putative causal gene than in sporadic cases, because in familial cases the spectrum of phenotypic anomalies is broader by compiling the various anomalies of affected relatives.…”
Section: Discussionmentioning
confidence: 75%
“…38) Costa and colleagues 32) screened NKX2-5 in 220 probands with adult-onset DCM, and found a novel missense mutation (p.I184M) in a proband, as well as two previously reported functional polymorphisms (p.R25C and p. A119S) in 2 other probands, with a mutational prevalence of about 1.36%. Genetic analysis of the mutation carrier's family showed that the mutation was present in all affected living adult family members.…”
Section: Discussionmentioning
confidence: 88%
“…In humans, NKX2-5 loss-of-function mutations have been previously implicated in familial adult-onset DCM, ASD, and arrhythmias, 32,33) of which the most commonly reported phenotypes are ASD and AVB in 68.4% and 65.7% of the cases, respectively. 38) Costa and colleagues 32) screened NKX2-5 in 220 probands with adult-onset DCM, and found a novel missense mutation (p.I184M) in a proband, as well as two previously reported functional polymorphisms (p.R25C and p. A119S) in 2 other probands, with a mutational prevalence of about 1.36%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations